2017
DOI: 10.1007/s12032-017-0892-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion (IVIM) Diffusion Weighted Imaging (DWI) in the Periferic Prostate Cancer Detection and Stratification

Abstract: The aim of this study was to compare the Intravoxel Incoherent Motion (IVIM) parameters between healthy Peripheral Zone (PZ), Benign Prostatic Hyperplasia (BPH) and Prostate Cancer (PCa) and compare them to assess whether there was correlation with Gleason Score (GS) grading system. Thirty-one patients with suspect of PCa underwent 1.5T Multi-Parametric Magnetic Resonance Imaging (MP-MRI) with endorectal coil with a protocol including T2WI, DWI using 10 b values (0, 10, 20, 30, 50, 80, 100, 200, 400, 1000 s/mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
7
33
0
2
Order By: Relevance
“…Intravoxel incoherent motion (IVIM) DWI is an advanced imaging technique that has been explored in various tumor types, including breast, liver, prostate, pancreas, and brain tumors . IVIM‐DWI with multiple b‐values can provide three parameters through biexponential analysis: the pure diffusion coefficient (D), perfusion‐related incoherent microcirculation (D*), and the microvascular volume fraction (f).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intravoxel incoherent motion (IVIM) DWI is an advanced imaging technique that has been explored in various tumor types, including breast, liver, prostate, pancreas, and brain tumors . IVIM‐DWI with multiple b‐values can provide three parameters through biexponential analysis: the pure diffusion coefficient (D), perfusion‐related incoherent microcirculation (D*), and the microvascular volume fraction (f).…”
mentioning
confidence: 99%
“…Intravoxel incoherent motion (IVIM) DWI is an advanced imaging technique that has been explored in various tumor types, including breast, liver, prostate, pancreas, and brain tumors. [9][10][11][12][13] IVIM-DWI with multiple b-values can provide three parameters through biexponential analysis: the pure diffusion coefficient (D), perfusion-related incoherent microcirculation (D*), and the microvascular volume fraction (f ). Compared to conditional DWI, IVIM-DWI can reflect both perfusion and true diffusion-related effect in tumors, thus more accurately characterizing the actual status of diffusion in tumors without a contrast agent.…”
mentioning
confidence: 99%
“…Gland Surg 2018;7(2):89-102 gs.amegroups.com enhancing low-signal-intensity regions are expected at sites of treated PCa (representing necrosis), while focal areas of enhancement (representing viable tissue) are suspicious for recurrence (65). In the last decades, a resurgent interest for functional imaging based on a special theory named intravoxel incoherent motion (IVIM) developed (66) and there are studies demonstrating that extract IVIM parameters in mpMRI is clinically relevant for PCa detection (67)(68)(69). One appealing feature of these data is that applying IVIM protocol, the perfusion information could be obtained without the need for intravenous contrast media (68,70,71), which is especially relevant considering nephrogenic systemic fibrosis due to the gadolinium-based contrast (72,73) and the rising concern of gadolinium deposition in neural tissues (74).…”
Section: Detection Of the Index Lesion To Be Treatedmentioning
confidence: 99%
“…Intravoxel incoherent motion (IVIM) is a diffusion model that aims to separate the perfusion effect from the diffusion effect. Some studies have applied IVIM in prostate imaging and showed promising results for the evaluation of prostate cancer 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%